2012
DOI: 10.1103/physrevstab.15.031302
|View full text |Cite
|
Sign up to set email alerts
|

Prism-coupled surface wave accelerator based on silicon carbide

Abstract: A compact, solid-state accelerating structure based on surface waves is proposed and experimentally characterized. The structure, consisting of two SiC layers epitaxially grown on Si slabs and separated from each other by a subwavelength acceleration channel, is shown to support both longitudinal (accelerating) and transverse (deflecting) surface modes. Both modes are experimentally excited and characterized by performing angle-resolved spectroscopy with a wavelength-tunable carbon dioxide laser. Phase velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The parameters are P x (0) = 0.01, P y (0) = 0.01, P z (0) = 0.09, x(0) = 0.01, y(0) = 0.01, t(0) = 0.0, f = π/2, E SP = 1.2 × 10 11 V/m, ω p = 1.3 × 10 16 rad/s, and the width of vacuum gap is a = 231 μm, that is, (aω p /c) = 100. The parameters used for this numerical analysis, are in agreement with the parameters used in the experimental and analytical studies by Zawadzka et al (2001), Liu et al (2007), Neuner et al (2012, and Kumar et al (2010). The kinetic energy gained by electrons with normalized distance have been ploted in Figure 5, with and without magnetic field.…”
Section: Electron Acceleration In the Presence Of A Magnetic Fieldmentioning
confidence: 78%
“…The parameters are P x (0) = 0.01, P y (0) = 0.01, P z (0) = 0.09, x(0) = 0.01, y(0) = 0.01, t(0) = 0.0, f = π/2, E SP = 1.2 × 10 11 V/m, ω p = 1.3 × 10 16 rad/s, and the width of vacuum gap is a = 231 μm, that is, (aω p /c) = 100. The parameters used for this numerical analysis, are in agreement with the parameters used in the experimental and analytical studies by Zawadzka et al (2001), Liu et al (2007), Neuner et al (2012, and Kumar et al (2010). The kinetic energy gained by electrons with normalized distance have been ploted in Figure 5, with and without magnetic field.…”
Section: Electron Acceleration In the Presence Of A Magnetic Fieldmentioning
confidence: 78%
“…As a result, at the interface between a bulk silicon substrate and a silicon carbide thin film, evanescent waves are supported. Schemes in which laser light is coupled into this structure via gratings and prisms have additionally been proposed [63,64]. These schemes have been tested for compatibility with CO 2 lasers.…”
Section: Slab Geometrymentioning
confidence: 99%
“…The linear theory of SPW propagation has already been studied on the interface of plasma and vacuum for cold, warm, unmagnetised and magnetised plasma. Recently, Neuner et al [7] and Liu et al [4] have reported their experimental as well as theoretical results for prism-coupled surface plasma wave (SPW) excitation for two metal surface configurations using low intensity lasers. H. J. Lee [8] investigated the electrostatic surface waves propagating on the plane interface between vacuum and cold magnetized homogeneous plasma.…”
Section: Introductionmentioning
confidence: 98%